The spectroscopic orbit of HD 168112 A,B in NGC 6604: another massive binary target for interferometry - Putkuri, Cristina Ester (2023)
We present the first spectroscopic orbit of the O-type double-lined star HD 168112 A,B. We analyse 101 high-resolution optical spectra identifying the absorption lines of both components. The orbital solution presents a relatively long period, P = 513.52 ± 0.01 d, and a high eccentricity, e = 0.743 ± 0.005. The binary system consists of two very similar stars of minimum masses of ~25 M⊙, effective temperatures of ~40 000 K, and surface gravities of ~3.7 dex. The system has a minimum semimajor axis a sin i ~ 1000 R⊙. We confirm that the A and B visual components identified via interferometry do correspond to the spectroscopic ones. We also analyse the underlying stellar groups using Gaia DR3 data and ground-based spectroscopy as part of the Villafranca project, determining that NGC 6604 is at a distance of 1942−36+38" role="presentation">1942+38−36 pc and giving spectral classifications for 23 massive stellar systems in Villafranca O-035 and the surrounding Ser OB2 association, for which we provide the most complete census of massive stars to date.